Scratch-based Science Interactive Animation Media to Improve Concept Understanding of Junior High School Learners - Sumalia, Rifa; Listiaji, Prasetyo (Journal for Lesson and Learning Studies, 2024)
The difficulty experienced in the learning process is the difficulty of understanding learning due to the lack of interesting material explanations and the availability of teaching materials in schools is still limited. This study aims to analyze the validity of scratch-based interactive animation media and how to improve students' concept understanding after using scratch-based interactive animation media. The research method used is Research and Development (R&D) by applying the ADDIE model. This study involved 34 students who underwent pretest-posttest trials to test the effectiveness of learning using the media. The evaluation in this study used two types of validation tools: material and media validation sheets assessed by five expert validators, and readability sheets filled out by learners. The validation results of this study show that the materials and media have a validity level of 93.25%, which indicates that the media is very valid. Readability by students reached 84%, indicating that the media was very practical to use. Based on these results, Scratch-based interactive animation media proved to be very feasible and effective to improve students' concept understanding.